Enantioselective resolution of 2-arylpropionic acid derivatives employing immobilization of lipase from Bacillus subtilis strain Kakrayal_1 (BSK-L). (December 2018) - Bhushan, Indu; Saraswat, Rashmi; Gupta, Pankaj; Shah, Bhahwal A.
Highlights: Lipase (BSK-L) was covalently immobilized on to APTES modified silica gel. Immobilization caused enhancement in the stability of lipase at adverse conditions. Immobilized lipase was reused and retained 85% of relative activity for 10 cycles. Immobilized showed higher enantioselectivity compared to free and commercial lipase. Abstract: This work studied the enantioselective resolution of 2-arylpropionic acid derivatives employing immobilization of lipase produced by Bacillus subtilis strain Kakrayal_1 (BSK-L). The efficient immobilization of lipase on modified silica gel was confirmed by Fourier transform infrared spectroscopy. Tethering of lipase facilitated the enhancement of physiochemical properties and stability of enzyme. Covalently immobilized enzyme retained 85% of residual activity even on reuse after 10th reaction cycle. Validation of immobilized lipase for enantioselective resolution of 2-arylpropionic acid derivatives led to 47.8% conversion efficiency with 87% enantiomeric excess (ee) for ketoprofen, and 27.3% conversion efficiency with 75% ee for flurbiprofen. The enantioselective resolution using immobilized lipase (BSK-L) was superior to free and commercially procured lipase, which suggest a potential application of immobilized lipase in the pharmaceutical/chemical industry.